Demonstratives in English and Arabic : A Contrastive Study (Journal of the College of Languages (JCL), 2006)
This paper studies the demonstratives as deictic expressions in Standard Arabic and English by outlining their phonological, syntactic and semantic properties in the two languages. On the basis of the outcome of this outline, a contrastive study of the linguistic properties of this group of deictic expressions in the two languages is conducted next. The aim is to find out what generalizations could be made from the results of this contrastive study.